SHIFTING BUSINESS ENVIRONMENT AND BORDER AREAS - Agustian Budi Prasetya (Jurnal Ilmiah Kajian Keimigrasian, 2021)
Abstract: Business environment transformation drives by the growth of internet-based technology and movement of goods and people migration across borders. The digital technology connects all nations, business actors and netizen within network ecosystem that make migrants across border engaged to the jurisdiction and nation sovereignty as well as engage to the similar civil rights, worker right and human rights and the global netizen. This article examines business competitiveness in Indonesia through borders management area. Method is desk research, utilizing academic references data. The discussion and analysis cover the ideas of managing synergetic multistakeholders in border area, positioning migrants as research, primary stakeholder that entitled for border area services and sources for investment opportunities, and conduct governance based on universal human rights, Indonesian national interest, as well as providing business certainty and security protection for migrants and foreigners